Cultura organizacional y satisfacción laboral en los trabajadores de la Universidad Marcelino Champagnat - Rojas Vásquez, Wilder Javier (2017)
The present research aimed to establish the relationship between organizational culture and job satisfaction in workers at Marcelino Champagnat University. The design was non-causal correlational. The population was 124, who were the majority of the workers at Marcelino Champagnat University who answered the Organizational Culture Inventory RST and the Job Satisfaction Scale RST. These instruments were subjected to expert judgment and validation tests. The results showed that a relationship was found between organizational culture and job satisfaction (r = .672; p = .000), as well as between its dimensions: Marist charisma - institutional norms and the dimensions of job satisfaction, showing that there is a highly significant relationship. It is concluded that there is a direct and significant relationship between organizational culture and job satisfaction. Likewise, there is a relationship between the Marist charisma dimension that has helped maintain institutional norms and that allow a good work environment. Each of these dimensions contributes to developing institutional identity, which is reflected in communication, the appreciation of work, the types of interpersonal relationships, workplace well-being, and the working conditions of the university's staff.